2018
DOI: 10.1139/cjas-2017-0134
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the response of hen weight, body composition, feather score, egg quality, and level of excreta nitrogen content to digestible balanced protein intake of laying hens

Abstract: Ideally balanced dietary protein is critical for laying hen egg production and feed efficiency, but also affects other important characteristics. This research was designed to study the nonegg production and feed intake response of Lohmann-LSL Lite hens to 550, 625, 700, 775, and 850 mg d−1 of amino acid balanced digestible lysine (Dlys) from 27 to 66 wk of age. Data collection included hen weight (HW), feather scoring, tissue weights, egg specific gravity, egg component weights, and excreta nitrogen (N) conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Deficiencies in dietary lysine alone have been associated with FP. Kumar et al (2018) fed several levels of dietary lysine to laying hens and measured their plumage over time (Figure 3). In total, five areas (neck, back, vent, wings and breast) were scored with each measurement a score from 1 (completely featherless) to 4 (fully feathered) at 27, 47 and 66 weeks of age.…”
Section: Dietary Protein and Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiencies in dietary lysine alone have been associated with FP. Kumar et al (2018) fed several levels of dietary lysine to laying hens and measured their plumage over time (Figure 3). In total, five areas (neck, back, vent, wings and breast) were scored with each measurement a score from 1 (completely featherless) to 4 (fully feathered) at 27, 47 and 66 weeks of age.…”
Section: Dietary Protein and Amino Acidsmentioning
confidence: 99%
“…Effect of lysine intake level (mg/hen/day) on mean cumulative feather score from 1 (completely featherless) to 4 (fully feathered) at five body areas: neck, back, vent, wings and breast, of laying hens fed different dietary lysine levels at 27 (black), 47 (striped) and 66 (dotted) weeks of age. Adapted from Kumar et al (2018).…”
Section: Dietary Protein and Amino Acidsmentioning
confidence: 99%
“…The eggs collected with cracked shells, prior to handling, were only considered to analyze this parameter. Studies have shown that egg shell quality (egg specific gravity) decreases with increasing EW as a result of increased daily dietary protein or AA consumption by laying hens (Gunawardana et al 2008b;Kumar et al 2018).…”
Section: Egg Productionmentioning
confidence: 99%
“…Feathers contain approximately 90% of protein, therefore the optimal ratios of limiting amino acids, in particular the sulfur-containing amino acids methionine (Met) and cystine (Cys), are indicated as necessary for the synthesis of feather keratin [ 4 , 10 , 11 , 12 , 13 ]. The sulfur-containing amino acid Cys is the major amino acid involved in the synthesis of feather keratin, which suggests a high dietary requirement of this amino acid [ 1 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%